Safety Needs Mediate Stressful Events Induced Mental Disorders - Zheng Zheng; Simeng Gu; Yu Lei; Shanshan Lu; Wei Wang; Yang Li; Fushun Wang (Neural Plasticity)
“Safety first,” we say these words almost every day, but we all take this for granted for what Maslow proposed in his famous theory of Hierarchy of Needs: safety needs come second to physiological needs. Here we propose that safety needs come before physiological needs. Safety needs are personal security, financial security, and health and well-being, which are more fundamental than physiological needs. Safety worrying is the major reason for mental disorders, such as anxiety, phobia, depression, and PTSD. The neural basis for safety is amygdala, LC/NE system, and corticotrophin-releasing hormone system, which can be regarded as a “safety circuitry,” whose major behavior function is “fight or flight” and “fear and anger” emotions. This is similar to the Appraisal theory for emotions: fear is due to the primary appraisal, which is related to safety of individual, while anger is due to secondary appraisal, which is related to coping with the unsafe situations. If coping is good, the individual will be happy; if coping failed, the individual will be sad or depressed.